Communication Model of the Technical Implementation Unit for the Protection of Women and Children in Accompanying and Protecting Child Victims of Sexual Violence in Riau Province - Rivai, Andi Kardian; Kholil, Syukur; Sikumbang, Ahmad Tamrin (Faculty of Law, Universitas Pekalongan, 2024)
This article aims to explore the implementation of the Communication Model by the Technical Implementation Unit for the Protection of Women and Children (UPT PPA) in assisting and protecting child victims of sexual violence in Riau Province. Given the increasing cases of sexual violence against children in Indonesia, this study highlights the importance of a comprehensive approach that integrates religious and cultural values to protect victims and support their recovery. Child sexual violence is an iceberg phenomenon in Indonesia, with many cases going unreported due to stigma and fear of social rejection. This study uses a qualitative approach to collect and analyze data on how UPT PPA Riau Province implements communication. The results show that the use of the Communication Model can increase the effectiveness of assistance, provide strong emotional support, and promote holistic recovery of victims. However, this study also identified several barriers, such as limited resources, lack of community understanding of Islamic values, and challenges in law enforcement. This article proposes strategies to overcome these barriers, including improving community education, strengthening institutional capacity, and using effective and empathetic communication in accordance with Islamic principles. This study contributes to the existing literature by showing how Islamic ethical and spiritual principles can be integrated into child protection practices to address and handle sexual violence.